Low-temperature formation of GeSn nanodots by Sn mediation. (29th May 2019) - Okamoto, Hiroshi; Takita, Kensuke; Tsushima, Kazuto; Tawara, Takehiko; Tateno, Kouta; Zhang, Guoqiang; Gotoh, Hideki
Abstract: GeSn is expected as a light-emitting material in Si photonics because a direct-bandgap nature appears with Sn composition above 10%. However, the emission wavelength of GeSn is in the mid-IR range. Thus, GeSn nanodots (NDs) are needed for telecom-wavelength emission. In this paper, we propose a formation method for GeSn NDs with Sn mediation. This process consists of low-temperature deposition of Sn and GeSn by vacuum evaporation and subsequent low-temperature annealing. Crystalline GeSn NDs with high density and high Sn content (more than 10%) have been successfully formed without metallic Sn precipitation or segregation of Sn on the dot surface. The possible formation mechanism of Sn-mediated GeSn NDs is also discussed.